XLambda: A Functional Programming Language with XML Syntax - Onder, Ruhsan; Bayram, Zeki (IEEE, 2009)
We describe XLambda, a functional language with XML syntax, and its processor which is implemented fully and completely in XSLT. X-Lambda has all the basic features of a functional language, such as defining named functions, operations on numbers, passing functions as parameters, constructing arbitrary data structures etc. What sets XLambda apart from the rest of the functional languages is not its feature set though, but rather its syntax and processor which is implemented as an XSLT stylesheet. Since most Web browsers have XSLT processors already built in, XLambda has the potential to be used as a scripting language in Browsers, much in the same way as JavaScript, among other possibilities.
24th International Symposium on Computer and Information Sciences -- SEP 14-16, 2009 -- Guzelyurt, CYPRUS